The Norwegian overnight interbank market during the Covid pandemic - Qaisar Farooq Akram; Jon Findreng; Lyndsie Smith (Norges Bank, 2023)
We analyse the behaviour of the Norwegian unsecured overnight interbank market in response to heightened uncertainty and the central bank's liquidity support measures following the Covid-19 pandemic. The liquidity measures enabled banks to fulfil their liquidity needs primarily through participation in extraordinary liquidity auctions. The distribution of central bank reserves across banks did not change due to these measures, but interbank trading fell sharply. Ample liquidity support through the auctions and low interbank trading contributed to low and overly stable overnight rates. Actually, throughout our sample period from 2017 to 2021, the overnight rates remained largely unaffected by fluctuations in uncertainty and overall liquidity conditions.
hdl:11250/3073371
Keywords: G21; E42; E47; E58; 330; The Covid-19 pandemic; distribution of central bank reserves; overnight interbank market; liquidity policy